ANALISIS PROSES PENETAPAN INDIKATOR KINERJA PADA ANGGARAN BERBASIS KINERJA DI PEMERINTAH KOTA MALANG - Restu Nur Rasyiidah Ihwan (Jurnal Ilmiah Mahasiswa FEB, 2015)
Performance is the basis for determine the APBD that began in 2003 ago. Things that need to be considered on the basis of this performance is the implementation of the budget resulting the performance gains of budget form, inputs, outputs, outcomes, benefits, impact and activities financed targeting accuracy. Until 2015 the implementation of performance-based budgeting is still not optimal. A measurable performance is an expectation that can not be achieved well. To be able to measure the performance relevant performance indicators needed, reliable and measurable. Althought the performance indicators only a small part of a series of APBD setting process, but if it is not well defined and are not able to describe the actual performance, the ideal performance measurement will not be achieved. This thesis aims to describe and analyze the process of establishing performance indicators in Malang city government. Researcher used descriptive method with qualitative approach and the data obtained is the primary data. The results showed that in the establishment of performance indicators in the local government adjusted and harmonized with regional and national programs. But it still not able to maximize the performance measurement because the indicators of outcomes, benefits and impact still difficult to determined. Keywords: Performance-Based Budgeting, Performance Indicators, Performance Measurement.